2004
DOI: 10.1159/000083473
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosant Therapy as First-Line Treatment for Solitary Liver Cysts

Abstract: Aim: The aim was to determine the outcome from percutaneous sclerosing treatment of solitary non-parasitic hepatic cysts. Methods: The results of treatment of patients with symptomatic solitary non-parasitic hepatic cysts treated between 1995 and 2000 were reviewed. Results: There were 23 women and one man with a median (range) age of 59 (34–79) years. The median (range) diameter of the cysts was 10 (5–24) cm. Five patients were treated by laparoscopic fenestration ab initio as they also required a cholecystec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…As the trend in the management of hepatic cysts continues to move towards minimally invasive approaches, alcohol sclerotherapy has been advocated as the first-line treatment for SHCs (18). Previous studies have suggested that multiple-session alcohol sclerotherapy can result in low recurrence rates, but it is associated with a higher risk of complications, whereas the single-session procedure is less risky but linked to a high recurrence rate (19).…”
Section: Discussionmentioning
confidence: 99%
“…As the trend in the management of hepatic cysts continues to move towards minimally invasive approaches, alcohol sclerotherapy has been advocated as the first-line treatment for SHCs (18). Previous studies have suggested that multiple-session alcohol sclerotherapy can result in low recurrence rates, but it is associated with a higher risk of complications, whereas the single-session procedure is less risky but linked to a high recurrence rate (19).…”
Section: Discussionmentioning
confidence: 99%
“…Sclerosants used include ethanol [12,19], tetracycline [20], minocycline, and pantopaque [21]. Percutaneous sclerotherapy is usually undertaken as a single-shot procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging data (Table 3) [12,19,20,[23][24][25][26][27][28][29][30] suggest that sclerotherapy could be a viable alternative to open/laparoscopic deroofing of cysts. However, no randomized controlled trial comparing the two modalities exists to date, and the differing end-points reported by most studies make comparison of the two procedures difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A congenital origin is supported by the occurrence of the cysts in fetuses and newborns, 636 by a case presenting as a congenital diaphragmatic hernia, 644 and the association of another case with the Peutz-Jeghers syndrome. 645 In the past, the treatment of choice of solitary cysts was excision, 646 but this has been supplanted by aspiration and sclerotherapy, 647,648 or laparoscopic fenestration. 649,650…”
Section: Solitary (Non-parasitic) Bile Duct Cystmentioning
confidence: 99%